High-Precision Compensation Method for Image Plane Deformation in the Doubly Telecentric Projection Optical System - Yuwei Xu; Hongbo Wu; Guangwei Shi; Haokun Ye; Jipeng Zhang; Yuqi Huang (Applied Sciences, 2025)
The deformation of the image plane due to gravity, clamping forces, and surface shape errors can significantly impact the exposure accuracy and imaging quality of the doubly telecentric projection optical system. To address the issues of resolution and image quality degradation resulting from non-conjugate image planes, this paper proposes a high-precision method for compensating image plane deformation using a dual-prism approach, establishes an analytical compensation model, and the theoretical derivation and quantification of the effects of compensation devices on image plane defocus, tilt, and aberration are provided. Compared to traditional simulation methods, the proposed approach offers a more predictable and precise compensation framework. The optimized design of the dual-prism compensation device has been validated through simulations, demonstrating the ability to control image plane deformation within 3.011 µm, which is smaller than the system’s depth of focus. The results indicate that this method significantly enhances the imaging accuracy of doubly telecentric projection optical systems and presents a novel theoretical tool for optimizing the design of optical compensation devices, thereby advancing the development of high-precision optical compensation technologies.